The Factors Influencing the Social Development Perception of Religious Leaders in the Zanzibar Urban Municipality - Nassor, Nassir; Zubeir, Yussuf Ramadhan; Hayeshi, Asha (International Journal of Global Community, 2026)
The study used an exploratory qualitative research design for participant selection and data collection. An interview method was applied to 42 religious leaders, comprising 22 Muslims, 14 Christians, 4 Buddhists, and 2 Hindus. This variation was based on the level of participants’ involvement in the research process; the sample size of 42 was determined by data saturation, a commonly used approach in qualitative research. Thematic analysis was employed to identify core themes and sub-themes, facilitating the interpretation of the study’s main ideas. The study’s findings show that the religious leaders’ perceptions of social development are shaped by their religious teachings and economy. The study concludes that religious leaders in urban Zanzibar perceive social development as a multifaceted interplay of religious, economic, and social factors. The study suggests that policy dynamics are crucial in fostering ethical and inclusive social change in Zanzibar.